High affinity anti-BSEP antibodies after liver transplantation for PFIC-2 - Successful treatment with immunoadsorption and B-cell depletion - Kubitz, Ralf; Dröge, Carola; Kluge, Stefanie; Stindt, Jan; Stross, Claudia; Häussinger, Dieter; Flechtenmacher, Christa; Wenning, Daniel; Teufel, Ulrike; Schmitt, Claus Peter; Engelmann, Guido (Pediatric transplantation, 2016)
PFIC due to BSEP mutations (PFIC type 2) often necessitates OLT. It has recently been recognized that some PFIC-2 patients develop phenotypic disease recurrence post-OLT due to the appearance of anti-BSEP antibodies. Here, we describe a boy who became cholestatic four yr after OLT during modification of immunosuppression. Canalicular antibody deposits were detected in biopsies of the transplant and antibodies specifically reacting with BSEP were identified at high titers in his serum. These antibodies bound extracellular epitopes of BSEP and inhibited BS transport and were assumed to cause disease recurrence. Consequently, anti-BSEP antibody depletion was pursued by IA and B-cell depletion by anti-CD20 antibodies (rituximab) along with a switch of immunosuppression. This treatment resulted in prolonged relief of symptoms. Depletion of pathogenic anti-BSEP antibodies causing AIBD after OLT in PFIC-2 patients should be considered as a central therapeutic goal.
Gesehen am 02.06.2020